Minimally Invasive Access to the Posterior Cranial Fossa: An Anatomical Study Comparing a Retrosigmoidal Endoscopic Approach to a Microscopic Approach - Van Rompaey, Jason; Bush, Carrie; McKinnon, Brian; Solares, Arturo C. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Objectives The central location and complex neurovascular structures of the posterior cranial fossa make tumor resection in this region challenging. The traditional surgical approach is a suboccipital craniotomy using a microscope for visualization. This approach necessitates a large surgical window and cerebellar retraction, which can result in patient morbidity. With the advances in endoscopic technology, minimally invasive access to the cerebellopontine angle can be achieved with minimal manipulation of uninvolved structures, reducing the complications associated with the suboccipital approach.Methods An endoscopic and microscopic approach was completed on anatomic specimens. To access the central structures of the posterior cranial fossa, a retrosigmoidal approach was undertaken. A keyhole craniotomy was made in the occipital bone posterior to the junction of the transverse and sigmoid sinuses. The endoscope was advanced and photographs were obtained for review. The exposure was compared with that obtained with a microscope.Results The endoscopic retrosigmoidal approach to the posterior cranial fossa provided increased exposure to the midline structures while minimizing the surgical window. The relevant anatomy was identified without difficulty.Conclusion An endoscopic retrosigmoidal approach to the midline structures of the posterior cranial fossa is anatomically feasible. The morbidity associated with retraction of the cerebellum could possibly be avoided, improving patient outcomes. Retrosigmoidal endoscopy provides access to anatomical structures that is not possible using a microscope in a suboccipital approach. Further understanding of the endoscopic anatomy of the posterior fossa can allow for advances in cranial base surgery with improved safety and efficacy.
Keywords: cerebellopontine angle; keyhole approach; endoscopy-assisted microsurgery; endoscopic retrosigmoidal approach; endoscopy-assisted microsurgery; intracranial tumor